Exploring management strategies to improve yield and mitigate nitrate leaching in a typical radish field in northern China. (15th July 2021) - Zhang, Jiajia; He, Wentian; Smith, Ward N.; Grant, Brian B.; Ding, Wencheng; Jiang, Rong; Zou, Guoyuan; Chen, Yanhua; He, Ping
Abstract: It is currently uncertain whether process-based models are capable of assessing crop yield and nitrogen (N) losses while helping to investigate best management practices from vegetable cropping systems. The objectives of this study were to (1) calibrate and evaluate the Denitrification-Decomposition (DNDC) model in simulating crop growth and nitrate leaching in a typical field radish system; (2) optimize management practices to improve radish yield and mitigate nitrate leaching under 20-year climate variability. A five-season in-situ field experiment of spring and autumn radish in northern China was established in the autumn of 2017 and measurements of radish yield, N uptake, soil temperature, soil moisture, drainage, and nitrate leaching were obtained under different N usage. DNDC overall demonstrated "good" to "excellent" performance in simulating radish yield, total biomass, N uptake, and soil temperature across all treatments (6.4% ≤ normalized root mean square error (nRMSE) ≤ 15.5%; 0.12 ≤ Nash-Sutcliffe efficiency (NSE) ≤ 0.88; 0.80 ≤ index of agreement (d) ≤ 0.97). DNDC generally exhibited "fair" performance in estimating soil moisture and drainage (10.9% ≤ nRMSE ≤ 27.2%; −0.18 ≤ NSE ≤ 0.37; 0.69 ≤ d ≤ 0.82) and "good" performance when predicting nitrate leaching (12.4% ≤ nRMSE ≤ 26.7%; −0.59 ≤ NSE ≤ 0.51; 0.68 ≤ d ≤ 0.90). Sensitivity analyses demonstrated that optimized management practices (planting dates, irrigation amount, fertilization rate and timing) could substantially reduce N usage by 40%–50%, irrigation amount by 33%–50%, and nitrate leaching by 86%–95% compared to farmers' practice in radish planting system. This study indicated that a modelling method is helpful for evaluating the biogeochemical effects of management alternatives and identifying optimal management practices in radish production systems of China. Graphical abstract: Image 1 Highlights: Denitrification-Decomposition (DNDC) was applied to simulate field radish systems. DNDC well simulated radish yield, nitrogen (N) uptake, and nitrate leaching. DNDC showed acceptable performance in simulating soil moisture and drainage. Modelled critical agronomic and environmental N rates were 150–180 kg N ha −1 . Optimized planting dates and irrigation rates improved yields and reduced N losses.